THE HALAL ASPECT AND ISLAMIC FINANCING AMONG MICRO, SMALL, AND MEDIUM ENTERPISES (MSMEs) IN YOGYAKARTA: DOES BERKAH MATTER? - Abdul Qoyum; Neneng Ela Fauziyyah (Journal of Islamic Monetary Economics and Finance, 2019)
The development of Halal industry points out an amazing result around the world, including Indonesia. Surprisingly, the biggest contributor for its growth is Micro, Small and Medium Enterprises (MSMEs). In order to improve its significant contribution, the combination of Halal MSMEs and Islamic financing becomes very crucial. Nevertheless, there is still a lack of awareness of the concept and of intention from MSMEs regarding the penetration of Islamic financing. Therefore, this study investigates the determinants affecting the MSMEs’ desire for utilizing Islamic financing from the Islamic financial institution and encouraging Halal MSMEs to adopt Islamic financing in all business activities. A survey was conducted on 58 MSMEs in Yogyakarta, Indonesia by employing self-administered questionnaire as the main approach for data collection. By using Structural Equation Modeling- Partial Least Square (SEM-PLS) analysis, this study reveals that from the variables examined, Cost Benefit and Halal Awareness are the two factors that have impact on the Use of Islamic Financing. In addition, Cost Benefit and Reputation are the two variables that have direct impact on the Attitude of MSMEs toward Islamic Financing. Interestingly, this research also finds that Berkah as the key component in Islamic financing will be gained by MSMEs when they use Islamic financing instrument, and, thus will encourage Halal MSMEs’ intention to reuse Islamic financing. Moreover, service quality and competitiveness are very crucial to maintain the customer satisfaction. In addition, preaching Berkah as key component in Muslim life is an important agenda in the future development of Halal Industry, especially in MSMEs sectors.